2015
DOI: 10.1016/j.wem.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Search and Rescue in Baxter State Park: Dangers of Descent and Fatigue

Abstract: Fatigue is a major factor in SAR events, both as a discreet cause and as a contributor to other injuries. Search and rescue need is more likely to occur during mountain descent, and lower extremity injuries are the most common etiology. Efforts should be focused on training rescuers in lower extremity and fatigue treatment, and more rescuers should be available when many are descending.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 9 publications
1
17
0
2
Order By: Relevance
“…Lower-limb injuries accounted for 54% of traumatic injuries. 5 These findings are similar to those of another Canadian study that used data from the Alpine Club of Canada, with a comparatively larger sample size (n=1088) but older cohort (1970–2005), and was broadly similar to previous studies in North America 2,3,4,7,8 and New Zealand. 1…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Lower-limb injuries accounted for 54% of traumatic injuries. 5 These findings are similar to those of another Canadian study that used data from the Alpine Club of Canada, with a comparatively larger sample size (n=1088) but older cohort (1970–2005), and was broadly similar to previous studies in North America 2,3,4,7,8 and New Zealand. 1…”
Section: Discussionsupporting
confidence: 88%
“…Our review of the literature identified 8 studies describing trends in medical search and rescue callouts. [1][2][3][4][5][6][7][8] Although some studies characterized health concerns as only traumatic or medical, others went further to identify the body region of injuries and the system of concern in medical callouts. A study that assessed emergency medical service (EMS) workload in Utah's national parks from 2001 to 2005 encompassed 4762 EMS incidents, with 79 fatalities and 1148 callouts described as firstaid.…”
Section: Emergency Medical Search and Rescue In Mountain Environmentsmentioning
confidence: 99%
“…3 In the United States, similar rates of heart problems and sudden death were reported for rescues in Denali (approximately 17%), and cardiac arrest after AMI was considered the largest single cause of death observed in Baxter State Park. 4,5…”
Section: Discussionmentioning
confidence: 99%
“…14 Slys voru mun algengari en veikindi og jafnvel enn algengari en áðurnefndar erlendar rannsóknir hafa sýnt. 2,3,4 Algengast var að fólk hrasaði, skrikaði fótur eða félli, sem leiddi til neðri útlimaáverka. Sú niðurstaða er í takt við erlendar rannsóknir og meistararitgerð Sigrúnar Guðnýjar Pétursdóttur.…”
Section: Umraeður Og áLyktanirunclassified
“…Sú niðurstaða er í takt við erlendar rannsóknir og meistararitgerð Sigrúnar Guðnýjar Pétursdóttur. 2,3,6 Ekki reyndist unnt að finna upplýsingar um frek ari ástaeður þessara atvika, hvort um lausagrjót var að raeða, fall vegna vindhviðu, misstig eða annað.…”
Section: Umraeður Og áLyktanirunclassified